Diagnostic accuracy of Enzyme-Linked Immunosorbent Assays to detect anti-Leishmania antibodies in patients with American Tegumentary Leishmaniasis: a systematic review - Zanetti, Andernice dos Santos; Sato, Camila Massae; Longhi, Fabiana Gulin; Ferreira, Silvana Margarida Benevides; Espinosa, Omar Ariel (Revista do Instituto de Medicina Tropical de São Paulo, 2019)
American Tegumentary leishmaniasis (ATL) is an infectious disease caused by several species of Leishmania. Even though the direct detection of parasites has low sensitivity, it is still the gold standard for the laboratory diagnosis of ATL. Recent studies have shown promising results of Enzyme-Linked Immunosorbent Assays (ELISAs) using recombinant antigens. The aim of this study is to compare the accuracy of ELISAs using novel antigens with the standard ELISA based on soluble antigens of Leishmania (SLA) to diagnose ATL. Studies that analyzed patients with ATL and studies that evaluated the diagnostic accuracy of ELISAs using novel antigens and SLA were included. The Fourteen studies from PubMed, Regional Portal of the Virtual Health Library (BVS), Brazilian Society of Dermatology, Virtual Health Library (IBECS), Literature in the Health Sciences in Latin America and the Caribbean (LILACS), Medical Literature Analysis and Retrieval System Online (Medline), Elsevier Embase, Cochrane Library, The National Institute for Health and Care Excellence (NICE), and Cumulative Index to Nursing and Allied Health Literature (CINAHL) were included. The novel ELISA antigens showed a high sensitivity (93.8%-100%) and specificity (82.5-100%), a better diagnostic performance than SLA-based ELISAs (1-97.4% and 57.5-100%, respectively). Only 10 studies analyzed cross-reactions in serum samples from patients with Chagas disease, and only two studies reported a percentage of cross-reactivity. In this systematic review, the novel ELISA antigens showed better sensitivity and specificity with respect to SLA-based ELISAs. However, a meta-analysis should be performed to confirm this finding.